Design of a freeform reflector for LED sources based on a feedback method. (May 2016) - Wu, H; Luo, C; Zhang, X; Ge, P; Zhang, X
We propose a method for the design of a freeform reflector by means of feedback methods to create light-emitting diode (LED) sources with uniform illuminance. A reflector is first designed to obtain a uniform circular light distribution for a point source. Then the optical performance of the reflector is investigated for both the point sources and extended sources based on a Monte Carlo ray tracing method. Comparing the illumination differences, a new reflector is generated by adding feedback. Repeated iterations of feedback can improve the reflector performance. To validate the method, a reflector is designed for an extended LED source. The results demonstrate that the illuminance uniformity can reach 88% and system efficiency can reach 97.4% simultaneously, after six feedback cycles. These are certainly able to meet the needs of general lighting applications.